2011
DOI: 10.1094/pdis-05-10-0346
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Weed Hosts of Tomato yellow leaf curl virus in Cyprus

Abstract: An extensive study was conducted during 2007 and 2008 in three major tomato production areas of Cyprus, where Tomato yellow leaf curl virus (TYLCV) is commonly found, to assess the incidence and prevalence of naturally infected weed species that could serve as TYLCV reservoirs. Approximately 4,000 of the most common dicotyledonous plants belonging to 122 species from 25 families were collected, identified, and tested for TYLCV presence using serological and molecular methods. The tests included a previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 34 publications
0
37
0
6
Order By: Relevance
“…TYLCV is transmitted by whiteflies and can spread rapidly; it is also not transmitted through seed or by mechanical transmission. Severe symptoms such as leaf curling, stunting, and yellowing showed on TYLCVinfected tomato plants, which cause serious production loss in tomato cultivation (Kil et al, 2016;Papayiannis et al, 2010). In addition to tomato, other cultivated plants including pepper (Capsicum species), common bean (Phaseolus vulgaris), cucurbit (Cucumis species) and eustoma (Eustoma grandiflora) have been reported to be TYLCV hosts (Anfoka et al, 2009;Kil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…TYLCV is transmitted by whiteflies and can spread rapidly; it is also not transmitted through seed or by mechanical transmission. Severe symptoms such as leaf curling, stunting, and yellowing showed on TYLCVinfected tomato plants, which cause serious production loss in tomato cultivation (Kil et al, 2016;Papayiannis et al, 2010). In addition to tomato, other cultivated plants including pepper (Capsicum species), common bean (Phaseolus vulgaris), cucurbit (Cucumis species) and eustoma (Eustoma grandiflora) have been reported to be TYLCV hosts (Anfoka et al, 2009;Kil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving different crops have also shown the importance of weeds as potential virus reservoirs to infect crops that are economically important and contributing to disease occurrence during the growing season, and also to virus dissemination (Ali et al, 2012;Papayiannis et al, 2011;Papayiannis et al, 2012;Solórzano-Morales et al, 2011;Asala et al, 2014). Additionally, weeds can still withstand drought in the field, and survive in the absence of preferred hosts, becoming an important initial source of virus inoculum, which can be spread not only to commercial crops, but also to infect other weed plants after harvesting periods (Asala et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological sig nificance of weeds in TYLCV transmission is well known, and their role as a virus reservoir during crop-free periods has been docu mented in previous reports (8,23). Surveys for TYLCV weed hosts have been conducted by numerous researchers from different coun tries (2,(10)(11)(12)17,19,22,23) and identified in a wide range of poten tial hosts, most of which were symptomless. However, most of these studies focused on vims detection from field samples; only some have focused on whitefly transmission analyses.…”
Section: Discussionmentioning
confidence: 99%
“…TYLCV is transmitted to host plants by the vector insect, sweet potato whitefly (.Bemisia tabaci) (7). TYLCV-infected tomato plants show symp toms including curling, interveinal yellowing of leaves, and severe stunting (17). Tomato yellow leaf curl disease (TYLCD) can cause severe tomato production loss.…”
mentioning
confidence: 99%
See 1 more Smart Citation